Lidocaine Gel for Transrectal Prostate Biopsy - Okigbeye, Danagogo; Victor, Abhulimen; Tamunotonye, Danagogo (International Journal of Innovative Research in Medical Science, 2023)
Introduction: Cancer of the prostate (CaP) is the most common cancer among black men. The incidence of prostate cancer is rising in Africa. Prostate biopsy is the standard procedure for the diagnosis of CaP. The prostate biopsy is an invasive procedure and is associated with pain. This can be emotionally and psychologically traumatic for the patient. Intrarectal gel administration is relatively non-invasive, easy to administer, cheap and has an acceptable time of onset of action. Methods: This is a prospective study to determine the analgesic effect of intrarectal lidocaine gel for digitally guided transrectal prostate biopsy. The study was carried out at the University of Port Harcourt Teaching Hospital. Ethical approval was sought and obtained from the hospital’s ethical committee. This is a tertiary institution in Port Harcourt the capital of Rivers State in southern Nigeria. The sample size was calculated to be 159. The patients then filled in the Visual Analogue Scale score (VAS) 5 minutes after the prostate biopsy. Results: The mean age of patients was 66.19 ±8.1. The mean prostate volume was 72.74±52.17. The mean VAS was 3.63±2.38 and over half 28(52.8%) of those in this group had mild pain while 17(32.1%) and 8(15.1%) had moderate and severe pain respectively. Conclusion: Lidocaine gel is a good option for analgesia during prostate biopsy. The analgesic effect of lidocaine gel for prostate biopsy is better when the contact time should be 30 minutes or more.